Pemanfaatan Nutricheck dan Comstock Elektronik untuk Optimalisasi Pemberian Makanan Tambahan Balita - Alfan Ridha; Ahmad Aufar Ribhi; Viki Hendi Kurniaditya; Zhairoh Hilwa Azizah; Bintang Galang Indra Prasetya (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Malnutrition among children under five, particularly stunting and wasting, remains a serious challenge in Indonesia. The 2022 Indonesian Nutritional Status Survey (SSGI) reported a stunting prevalence of 21.6% and wasting prevalence of 7.1%, which may hinder the achievement of the national target to reduce stunting by 2024. The Supplementary Feeding Program (PMT) at Posyandu plays a strategic role in addressing this issue; however, its implementation is often constrained by cadres’ limited ability to design balanced menus, calculate nutritional needs, and conduct data-based evaluations. This community service program was carried out at Posyandu Melati 6, Madegondo Village, Sukoharjo, aiming to strengthen cadres’ capacity through the utilization of Nutricheck for nutrient calculation and Electronic Comstock for evaluating children’s food consumption. The methods included socialization, training, menu development practice, mentoring, and evaluation. The results showed a significant increase in cadres’ knowledge with an average improvement of 54% in post-test scores, the development of 14 variations of supplementary feeding menus based on local food, and a high acceptance rate among children (70% finished their portions). Data obtained from Electronic Comstock provided objective evidence to support menu adjustments. These findings highlight the importance of integrating simple digital tools into the optimization of locally based supplementary feeding as a strategy to prevent stunting and improve child nutrition.